Expansion of functions in a system of polynomials biorthogonal on a closed contour with a system of functions regular at infinitely remote point - Sukhorolskyi, M. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We study properties of the systems of polynomials constructed according to the schemes similar to the schemes used for the Bernoulli and Euler polynomials, formulate conditions for the existence of functions associated with polynomials and conditions of representation of polynomials by contour integrals, and present the classes of analytic functions expandable in series in the systems of polynomials. The expansions of functions are illustrated by examples.